(untitled) - Fraenkel, Peter (London, 1986)
The book surveys the water-lifting technologies which are available and appropriate for smllholdings - defined here as areas up to twenty-five hectares - and produces detaled guidance on the suitability of different methods of water-lifting in differents situations. Human-and animal-power; internal and external combustion systems; electrical, wind, solar and hydro-power; and the uses of biomass and coal - are all surveyed in detail, in relation to mechanical capability as well as costs, reliability and availability.
Keywords: Mechanical engineering,Pumps